Nanophotonics and plasmonics an integrated view - Png, Ching Eng; Akimov, Yuriy (Series in optics and optoelectronics, 2017)
This book provides a first integrated view of nanophotonics and plasmonics, covering the use of dielectric, semiconductor, and metal nanostructures to manipulate light at the nanometer scale. Ultimately, the goal is to provide a basis for developing a unified platform for both fields. In addition to the fundamentals and detailed theoretical background, the book showcases the main device applications.